ANALYSIS OF STUDENTS’ SATISFACTION ON THE QUALITY OF ATM SERVICES AT BANK SYARIAH INDONESIA IN JAMBI CITY - Ahmad Syahrizal; Anik Anik; Pijai Pijai (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to determine the extent of student satisfaction in Islamic Banking Faculty of Economics and Islamic Business UIN Sultan Thaha Saifuddin Jambi on the quality of Automatic Teller Machine (ATM) services provided by Sharia Bank of Indonesia (Bank Syariah Indonesia) in Jambi City by looking at the influence of the dimensions of physical evidence, reliability, responsiveness, assurance, and empathy. The approach in this research is a quantitative method using multiple linear regression analysis with a sample of students of the Islamic Banking Study Program who are active users of Automatic Teller Machine (ATM) services. The results showed that of the five dimensions of service quality measurement, it was found that three dimensions, namely physical evidence, reliability, and assurance, had a positive and significant effect on student satisfaction, while the responsiveness dimension had a negative effect and the empathy dimension did not affect student satisfaction.